2017
DOI: 10.3389/fimmu.2017.01858
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer T Cells: An Ecological Evolutionary Developmental Biology Perspective

Abstract: Type I natural killer T (NKT) cells are innate-like T lymphocytes that recognize glycolipid antigens presented by the MHC class I-like protein CD1d. Agonistic activation of NKT cells leads to rapid pro-inflammatory and immune modulatory cytokine and chemokine responses. This property of NKT cells, in conjunction with their interactions with antigen-presenting cells, controls downstream innate and adaptive immune responses against cancers and infectious diseases, as well as in several inflammatory disorders. NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 254 publications
0
72
0
Order By: Relevance
“…Innate‐like T lymphocytes, such as NKT cells, recognize GSLs presented by CD1d and control innate and adaptive immune responses against not only some inflammatory diseases but also against cancers and infectious diseases . It has been found that a marine sponge‐derived α‐GalCer is a lipid antigen molecule, which activates NKT cells .…”
Section: Gsls As Immune Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate‐like T lymphocytes, such as NKT cells, recognize GSLs presented by CD1d and control innate and adaptive immune responses against not only some inflammatory diseases but also against cancers and infectious diseases . It has been found that a marine sponge‐derived α‐GalCer is a lipid antigen molecule, which activates NKT cells .…”
Section: Gsls As Immune Modulatorsmentioning
confidence: 99%
“…GQ1b and α‐GalCer were shown to function as immunomodulators . Moreover, α‐GalCer, derived from a marine sponge, was found to act as a lipid antigen that activates natural killer T (NKT) cells , which control innate and adaptive immune responses . α‐Linked glycosylceramides were shown to be the major endogenous ligands of NKT cells .…”
mentioning
confidence: 99%
“…Invariant natural killer T (iNKT) cells are a distinct T cell lineage that expresses an invariant Vα14-Jα18 TCR in mice (Vα24-Jα18 in humans) combined with a limited TCRβ repertoire and surface markers that are typically associated with NK cells. iNKT cells recognize glycolipid antigens presented by the MHC class I-like molecule CD1d and are a functional bridge between the initial innate immune response and subsequent adaptive response 1 . Upon activation, iNKT cells play a protective or detrimental role in infectious and autoimmune diseases and mediate tumor surveillance by rapidly secreting copious levels of cytokines such as interferon-γ (IFN-γ) and interleukin 4 (IL-4) and activating diverse immune cells 2 5 .…”
Section: Introductionmentioning
confidence: 99%
“…iNKT cells are mostly generated in the thymus from CD4 + CD8 + double-positive (DP) thymocytes, similar to the generation of conventional T cells. There are four distinct stages of iNKT cell development based on CD24, CD44 and NK1.1 expression on TCRαβ + T cells that react with the CD1d tetramer loaded with the α-GalCer analog PBS57 (CD1d-PBS57) 1 , 9 12 . The earliest iNKT cell precursors (stage 0) are derived from DP thymocytes and are defined as CD24 high CD44 lo NK1.1 lo .…”
Section: Introductionmentioning
confidence: 99%
“…Similar occurrences of cells with bipotential nature such as the CD1-restricted natural killer T cell have also been subject to study (Melinda A. Borrello & Phipps, 1995. Regarding the evolution of the natural killer T cell, it is thought to be a result of CD1 genes evolving rapidly and diverging substantially from the reptiles within eutherian species (Kumar et al, 2017), which differ from both of the above hypothesizes of B-1 evolution. It is unknown whether a subset of these cells exist in reptiles, but there has been discovery of the CD1 gene mentioned earlier.…”
Section: │ Humoral Immunitymentioning
confidence: 99%